Modelo de transferência de tecnologias da indústria 4.0 para suporte à implementação tecnológica no setor de avicultura de corte - Silva, Vander Luiz da (2023)
Industrial revolutions were the main drivers of changes imposed in organizational and labor scenarios. In the case of the recent industrial configuration approach, called Industry 4.0, processes acquire artificial intelligence, data collection increases, and connectivity between resources expands. If interested, companies need to apply investments towards the transition to Industry 4.0, which will depend on the successful implementation of technologies. This study aimed to propose a Technology Transfer Model 4.0 (TTM4.0) to support technological implementation. From the extensive literature review, a model was proposed, whose TT is emphasized from the perspective of the transferee. Once proposed, to demonstrate a practical approach, two case studies in the poultry industry are presented. In Brazil, poultry industry is a driver of the economy and generates important repercussions in the country's socioeconomic indexes; however, it has a low level in technological maturity compared to other sectors. In the application of TTM4.0, to measure TT elements and manage decisions, the AHP, Likert and Fuzzy-TOPSIS standards were used, respectively. As for the similar results among case studies 1 and 2, thinking about Industry 4.0, the main strategic needs were product quality, reduction of human error and reduction of waste. Among the main inhibiting factors of interest and availability by Industry 4.0 are the need for high investment, lack of knowledge in Industry 4.0, uncertainties in results and difficulties in relocating people at work. Results commonly indicate Big Data Analytics and artificial intelligence technologies to the poultry industry, based on the applicability in Industry 4.0 and case studies. Industry 4.0 has strong direction to the concept of an intelligent industry, where there is connectivity between technological resources, people, departments and companies. Studies in Technology Transfer in Industry 4.0 are suggested, presenting results of technological implementations in monitoring and/or effected, and impacts of TT on the adoption of Industry 4.0.